Sex Related Differences in Electrocardiography - Kittnar, Otomar (Physiological research, 2023)
Since its implementation into the clinical medicine by Willem Einthoven electrocardiography had become one of crucial diagnostic method in cardiology. In spite of this fact effects of gender differences on parameters of electrocardiographic recordings started to be studied only recently. Sex related differences in physiological ECG are only minimal in childhood but there are developing during adolescence reflecting rapidly evolving differences particularly in hormonal secretion and activity of an autonomic nervous system. The heart rate is approximately 7 % higher in women than in men, PQ and QRS intervals are longer in men while QT interval is longer in women. The ST segment in females is flatter but generally the sex-related differences in ST-T waveform patterns are relatively very small with higher level of ST segment and taller T wave in men. The effects of sex-related differences, including sex hormones, on cardiac cell injury and death and their influence in determining rhythmogenesis and action potential configuration and conduction play an important role in clinics. Women have a higher prevalence of sick sinus syndrome, inappropriate sinus tachycardia, atrioventricular nodal reentry tachycardia, idiopathic right ventricular tachycardia, and arrhythmic events in the long QT syndrome. In contrast, men have a higher prevalence of atrioventricular block, carotid sinus syndrome, atrial fibrillation, supraventricular tachycardia due to accessory pathways, Wolff-Parkinson-White syndrome, reentrant ventricular tachycardia, ventricular fibrillation and sudden death, and the Brugada syndrome.